PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DEVIDEND PAYOUT RATIO (DPR) - Eka Sartika Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2014)
Eka Sartika Sari; The purpose of this observation to know the factors effect that affect Dividend Payout Ratio (DPR) wisdom at manufacturing company registered in Bursa Efek Indonesia. The used of data is financial report annual from 18 manufacturing company which registered in Bursa Efek Indonesia during 2007 until 2011. Analiysis method which used is multiple regression linear. Variable in this observation are Size, Liquidity, Profitability, Growth, and Institutional Owner as independend variable. While the dependent variable is Payout Ration Dividend Wisdom (DPR). The independend variable was did with Simultan and Partial test using SPSS. The observation result show that company Proportion, Liquidity, Profitability, Company Growth, and Institutional Owner whether is Simultan or in Partial, it is not take siginificant effect to Dividend Payout Ratio (DPR). Key words: Dividend Payout Ratio (DPR), Size, Liquidity, Profitability, Growth and Institutional Owner